Genetic pleiotropy of ERCC6 loss‐of‐function and deleterious missense variants links retinal dystrophy, arrhythmia, and immunodeficiency in diverse ancestries. Issue 8 (31st May 2021) - Forrest, Iain S.; Chaudhary, Kumardeep; Vy, Ha My T.; Bafna, Shantanu; Kim, Soyeon; Won, Hong‐Hee; Loos, Ruth J.F.; Cho, Judy; Pasquale, Louis R.; Nadkarni, Girish N.; Rocheleau, Ghislain; Do, Ron
Abstract: Biobanks with exomes linked to electronic health records (EHRs) enable the study of genetic pleiotropy between rare variants and seemingly disparate diseases. We performed robust clinical phenotyping of rare, putatively deleterious variants (loss‐of‐function [LoF] and deleterious missense variants) in ERCC6, a gene implicated in inherited retinal disease. We analyzed 213, 084 exomes, along with a targeted set of retinal, cardiac, and immune phenotypes from two large‐scale EHR‐linked biobanks. In the primary analysis, a burden of deleterious variants in ERCC6 was strongly associated with (1) retinal disorders; (2) cardiac and electrocardiogram perturbations; and (3) immunodeficiency and decreased immunoglobulin levels. Meta‐analysis of results from the Bio Me Biobank and UK Biobank showed a significant association of deleterious ERCC6 burden with retinal dystrophy (odds ratio [OR] = 2.6, 95% confidence interval [CI]: 1.5‐4.6; p = 8.7 × 10 −4 ), atypical atrial flutter (OR = 3.5, 95% CI: 1.9‐6.5; p = 6.2 × 10 −5 ), arrhythmia (OR = 1.5, 95% CI: 1.2–2.0; p = 2.7 × 10 −3 ), and lymphocyte immunodeficiency (OR = 3.8, 95% CI: 2.1–6.8; p = 5.0 × 10 −6 ). Carriers of ERCC6 LoF variants who lacked a diagnosis of these conditions exhibited increased symptoms, indicating underdiagnosis. These results reveal a unique genetic link among retinal, cardiac, and immune disorders and underscore the value of EHR‐linked biobanks in assessing the full clinical profile of carriers of rare variants. Abstract : Excision repair cross‐complementing group 6 (ERCC6) is a DNA repair gene implicated in inherited retinal disease and the autosomal recessive multi‐system disorder Cockayne Syndrome B (CSB). In this study of 213084 participants from two large‐scale multi‐ethnic biobanks with exome and electronic health record data, we identified 4679 heterozygote carriers of rare deleterious ERCC6 variants and uncovered clinical evidence of pleiotropy with similar retinal, cardiac, and immune phenotypes as in CSB. Carriers were of diverse ancestries and underdiagnosed for pleiotropic conditions.